The sequence characteristics and functions on regulating trehalose metabolism of two PTP genes in Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae). (December 2020) - Pan, Bi-ying; Xu, Kang-kang; Luo, Yu-jia; Wang, Yuan-yuan; Zhou, Min; Li, Can; Tang, Bin
Abstract : Protein tyrosine phosphatase is a type of enzyme commonly found in eukaryotes that specifically hydrolyzes tyrosine phosphate bonds on protein substrates to remove phosphate, thereby regulating protein functions or even cell functions. In this study, we used the model insect Tribolium castaneum to study the sequence characteristics and functions on trehalose metabolism of two PTP proteins in T. castaneum . We found that TcPTP1X1 and TcPTPIVA1 contain 190 and 177 amino acids, respectively. The results of phylogenetic analysis showed that PTP1 and PTPIVA1 are less well conserved across insect lineages. Examining the tissue and developmental expression patterns revealed that TcPTP1X1 and TcPTPIVA1 are expressed in various tissues and stages of T. castaneum ; they are highly expressed in the tarsus during the pupal and adult stages. Compared with the negative control dsGFP group, almost all trehalase and 6-trehalose phosphate synthase genes were significantly down-regulated at 48 h after injection with dsPTP1X1 or dsPTPIVA1, except TRE1-3 . At 72 h, many of the TRE and TPS genes appeared to return to normal levels or were even significantly upregulated compared with the control group. Silencing of TcPTP1X1 or TcPTPIVA1 altered the distribution of trehalose, glucose and glycogen in T. castaneum . Moreover, suppression of TcPTP1X1 or TcPTPIVA1 expression resulted in reduced adenosine triphosphate (ATP) content. We suggest that knockdown of TcPTP1X1 or TcPTPIVA1 impairs trehalose and energy metabolism in T. castaneum, and they may be new targets for control of storage pests. Highlights: PTP1 and PTPIVA1 are highly conserved across insect lineages. TcPTP1X1 and TcPTPIVA1 are expressed in different tissues at various stages. Inhibition of TcPTP1X1 or TcPTPIVA1 disrupts the carbohydrate homeostasis. Downregulation of TcPTP1X1 or TcPTPIVA1 resulted in reduced ATP content.